Content–oriented learning recommendation mechanism in MANETs. (27th May 2014) - Hung, Lun–Ping; Park, James J.; Chu, Kuo–Chung; Yen, Neil Y.
With the ever–growing needs for personal learning, a multidimensional mechanism that aims at providing tailored educational contents in an open environment in this study. This mechanism is implemented in an intelligent tutoring system (ITS), which primarily consists of three interactive modules for learning content delivery. The self–organising map (SOM) is applied to the analysis of the factors (e.g., individual needs, preferences, etc.) and as the main process towards the delivery of recommendations and achieve personalisation. Results demonstrate that the proposed mechanism gives a solution to the issue of information overload and enhances interest and efficiency for personal learning. Contributions include: 1) the cost of time on obtaining useful learning content in an open environment is reduced; 2) the chance towards socially–learning scenario with personalised learning support is achieved.